The protective effect of curcumin on thrombin-induced hyper-permeability - Farzad Rahmani; Hossein Abdeahad; Najmeh Jaberi; Reyhane Hanaie; Atena Soleimani; Amir Avan; Majid Khazaei; Seyed Mahdi Hassanian Mehr (Avicenna Journal of Phytomedicine, 2023)
Objective: Thrombin is a proinflammatory and pro-coagulant agent which is upregulated in several human diseases. Thrombin has a critical role in promoting cell proliferation and microvascular leakage in malignant cells, resulting in cancer growth and progression. Here, we explored the potential therapeutic value of curcumin on permeability induced by thrombin in mice.Materials and Methods: To assess the activity of curcumin on thrombin-induced vascular permeability mice model, C57BL / 6 mice were randomly divided into four groups: (1) control (2) Thrombin (3) Thrombin + Curcumin and (4) Thrombin + Metformin. Thirty minutes after treatment, Evans blue was injected intravenously through the tail vein to mice. Then, animals were sacrificed and the dye was extracted from the skin tissue by incubation with formamide. Heatmap and correlation map were generated and protein-protein interaction network of the hub genes was drawn by Cytoscape software.Results: Hub DEG expression rate showed that Heat shock protein a1 (Hspa1) family (comprised of HSPa1a, b, and HSPa5), caspase 3, and minichromosome maintenance complex component 2 were overexpressed after treatment with curcumin. Functional modules of curcumin enriched through Enrich gene biological process and revealed positive association of gene expression of apoptosis process with the therapy. Curcumin was also found to reduce leucocyte migration in murine tissues. Additionally, treatment with curcumin resulted in downregulation of heat shock proteins and proinflammatory cytokines such as monocyte chemotactic protein 1, interleukin-6 and chemokine (C-X-C motif) ligand 3.Conclusion: Curcumin inhibited the proinflammatory cytokines and inflammatory HSPs in endothelial cells and reduced thrombin-induced barrier destabilization in vivo.